2018
DOI: 10.1016/j.jelekin.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in jaw clenching force control in people with myogenic temporomandibular disorders

Abstract: Isometric bite force control, via measures of force accuracy, force steadiness and force proprioception, was assessed in patients with myogenic temporomandibular disorders (TMDs) compared to healthy controls. Twelve people with myogenic TMDs and twelve age-and gender-matched asymptomatic controls performed maximal voluntary contractions (MVC) of unilateral jaw clenching followed by submaximal isometric contractions, with and without visual feedback of force, at 10, 30 50% and 70% MVC. Force performance was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…The results are in line with those observed by other authors, who found that the decrease in masticatory muscle pain intensity led to an increase in BF [46]. Another set of studies evaluating the BF of patients with TMD in comparison with healthy subjects found that the masticatory MVC was reduced in the group of participants with TMD [8,47]. Cho and Lee [7] obtained similar results, since they found that the presence of pain led to a decrease in BF, although it is necessary to emphasize that in these studies, pain was experimentally induced.…”
Section: Bite Force and Neuromuscular Activation Of Masticatory Musclessupporting
confidence: 91%
“…The results are in line with those observed by other authors, who found that the decrease in masticatory muscle pain intensity led to an increase in BF [46]. Another set of studies evaluating the BF of patients with TMD in comparison with healthy subjects found that the masticatory MVC was reduced in the group of participants with TMD [8,47]. Cho and Lee [7] obtained similar results, since they found that the presence of pain led to a decrease in BF, although it is necessary to emphasize that in these studies, pain was experimentally induced.…”
Section: Bite Force and Neuromuscular Activation Of Masticatory Musclessupporting
confidence: 91%
“…To the best of our knowledge, there are no data on whether patients with painful TMD bite with higher forces than non‐TMD subjects. On the other hand, force control at low level is not impaired in myogenous patients 42 . Fifth, TMD‐pain lasted for less than 6 months, and in only one half of them, the pain had an impact on their daily life.…”
Section: Discussionmentioning
confidence: 94%
“…This is unfortunate for sleep bruxism studies, in which individuals with pain in the masticatory system are often investigated. It has been shown that the force, measured in N, which is exerted during maximal contraction on force transducers, is decreased in individuals with pain in the masticatory system, compared to pain‐free controls 142,143 . In addition, Manfredini et al found that in individuals with myofascial pain the level of EMG activity of masticatory muscles was significantly lower compared to pain‐free controls, during maximum clenching on cotton rolls 144 .…”
Section: Discussionmentioning
confidence: 99%